Cytotoxic roles of apigenin and kaempferol on staurosporine-treated mesenchymal stem cells in an in vitro culture - Kosiedowska Magdalena; Burczak Arkadiusz; Morys Julia; Borkowska Paulina; Kowalski Jan (Herba Polonica, 2021)
Flavonoids are widely distributed in the wild. They constitute a large group of compounds that have a beneficial effect on the human body. Apigenin and kaempferol, which belong to the flavone subgroup, have, inter alia, an antitumor effect. The influence of these compounds on the survival of stem cells in a toxic environment has not yet been studied.